PENGARUH ORIENTASI PASAR, ORIENTASI PEMBELAJARAN DAN INOVASI PRODUK TERHADAP KINERJA PEMASARAN (STUDI KASUS PADA UMKM WARUNG KOPI DI DIY) - Abdurrahman Abdurrahman; Ida Bagus Nyoman Udayana; Lusia Tria Hatmanti Hutami (SEGMEN: Jurnal Manajemen dan Bisnis, 2022)
This research was conducted to analyze the variables that affect the marketing performance of MSME Coffee Shops in DIY. The independent variables consist of Market Orientation (X1), Learning Orientation (X2), and Product Innovation (X3). The dependent variable is marketing performance (Y).Samples taken are employees, managers and marketing management of UMKM Coffee Shops in DIY who have worked at UMKM Coffee Shops in DIY. The number of samples taken is 100 respondents using positive sampling technique. The analysis tool used is SPSS 20.Based on the results of the analysis and discussion using multiple regression analysis, it shows that market orientation, learning orientation and product innovation have a significant positive effect on marketing performance. Partially market orientation has a significant positive effect on marketing performance, learning orientation partially has no significant effect on marketing performance, while simultaneously product innovation d has a significant positive effect on marketing performanceKeywords: Market Orientation, Learning Orientation, Product Innovation, Marketing Performance